Kossmaticeras in North Greenland. (August 2018) - Alsen, Peter
Abstract: Kilen in Kronprins Christian Land in eastern North Greenland provides a rare opportunity to study Late Cretaceous faunas at high northern latitudes. A well-preserved fauna discovered in concretions includes a rich assemblage of small kossmaticeratid ammonites, which represent a new species, Kossmaticeras ( Kossmaticeras ) kilenense sp. nov.